4(9-x)0.5-6=10

Add 6 to both sides of the equation.

4(9-x)0.5=10+6

Add 10 and 6.

4(9-x)0.5=16

4(9-x)0.5=16

Divide each term in 4(9-x)0.5=16 by 4.

4(9-x)0.54=164

Cancel the common factor of 4.

Cancel the common factor.

4(9-x)0.54=164

Divide (9-x)0.5 by 1.

(9-x)0.5=164

(9-x)0.5=164

Divide 16 by 4.

(9-x)0.5=4

(9-x)0.5=4

Convert the decimal number to a fraction by placing the decimal number over a power of ten. Since there is 1 number to the right of the decimal point, place the decimal number over 101 (10). Next, add the whole number to the left of the decimal.

(9-x)510=4

Cancel the common factor of 5 and 10.

Factor 5 out of 5.

(9-x)5(1)10=4

Cancel the common factors.

Factor 5 out of 10.

(9-x)5⋅15⋅2=4

Cancel the common factor.

(9-x)5⋅15⋅2=4

Rewrite the expression.

(9-x)12=4

(9-x)12=4

(9-x)12=4

(9-x)12=4

Raise each side of the equation to the 2 power to eliminate the fractional exponent on the left side.

((9-x)12)2=(4)2

Raise 4 to the power of 2.

9-x=16

Move all terms not containing x to the right side of the equation.

Subtract 9 from both sides of the equation.

-x=16-9

Subtract 9 from 16.

-x=7

-x=7

Multiply each term in -x=7 by -1

Multiply each term in -x=7 by -1.

(-x)⋅-1=7⋅-1

Multiply (-x)⋅-1.

Multiply -1 by -1.

1x=7⋅-1

Multiply x by 1.

x=7⋅-1

x=7⋅-1

Multiply 7 by -1.

x=-7

x=-7

x=-7

Solve for x 4(9-x)^0.5-6=10